공검지 습지보호지역의 식생 구조와 분포 및 보전을 위한 제안 - 이철호(Cheolho Lee); 김휘래(Hwirae Kim); 박소현(So Hyun Park); 추연수(Yeounsu Chu); 윤정도(Jungdo Yoon); 조강현(Kang-Hyun Cho) (Ecology and Resilient Infrastructure, 2019)
The Gonggeomji Reservoir is a historical irrigation facility built in the 8th century and designated as a wetland protected area by Ministry of Environment, Korea. In order to collect the baseline data necessary for developing a sustainable conservation strategy, we investigated the classification of actual vegetation, the vegetation distribution and the floristic structure of the vegetation in the Gonggeomji Wetland Protection Area. In the whole protection area, a total of 26 plant communities were classified including the wetland, riparian, grassland, forest, farmland, and orchard vegetation. According to the results of detrended correspondence analysis, the structure of wetland vegetation was mainly affected by water depth and human disturbance. In reservoir wetlands, floating vegetation such as Utricularia vulgaris var. japonica, Trapa japonica, and emergent vegetation such as Nelumbo nucifera, Typha spp. completely covered the water surface. Since 2014, the reservoir wetland has been terrestrialized with the expansion of emergent and hygrophytic plants. For the sustainable conservation and restoration of wetland protected areas, it is necessary to naturalize the topography and wetland vegetation, recovery the hydrologic system, and restore ecosystem connectivity from wetlands to forests. 상주 공검지는 8세기에 축조된 고대 유적 저수지로서 습지보호지역으로 지정되어 있다. 이곳에서 지속가능한 보전 전략을 수립하는데 필요한 기초자료를 수집하기 위하여, 현존 식생을 분류하고 식생도를 작도하며 식생의 구조적 특징을 파악하고 환경과의 관계를 규명하였다. 공검지 습지보호지역에서는 저습지, 하천, 산림, 초지, 농경지, 과수원 식생에 속하는 총 26개 식물군집이 분류되었다. 탈경향대응분석 (detrended correspondence analysis) 결과에 따르면 습지 식생의 구조는 주로 수심과 인간 교란에 따라서 영향을 받았다. 저수지 습지에서는 통발, 마름과 같은 부수식물과 연꽃, 부들류와 같은 정수식물이 수면을 완전히 피복하고 있었다. 2014년 이후에 점차 정수식물과 습생식물의 분포 면적이 늘어나는 육역화가 빠르게 진행되고 있었다. 습지보호지역의 지속가능한 보전과 복원을 위하여, 지형과 식생을 복원하고, 수문 체계를 회복시키며, 습지로부터 산지까지의 생태계 연결성을 회복한 것이 필요하다고 생각된다.